Implementing Evidence-Based Practice: A challenge for the nursing practice - Barría P., R. Mauricio (Investigación y Educación en Enfermería, 2014)
Research in nursing has evidenced sustained increase during recent decades, responding to the need to strengthen the scientific base of the practice, as a way of providing cost-effective care and implementing prevention and promotion strategies that are pertinent to the contexts. Consequently, it would be expected that using research in the customary practice would progress likewise through an Evidence-Based Practice (EBP). Nevertheless, although it would be evaluated as an opportunity and need for quality caregiving, research has been relegated to the academic context and distant from the everyday work of the practice.1 To bridge the gap between research and practice, it is emphasized that EBP can contribute to: developing clinical practice guides, updating knowledge, developing nursing as science, improving the credibility of nurses as autonomous professionals, improving health results of patients and limiting health costs, and using in timely manner results of updated and reliable research to improve the quality of healthcare attention.2 In turn, adoption of an EBP can be seen from the perspective of those who investigate or generate knowledge, those who use the information based on evidence, and those who serve as binding links between generators and users of knowledge.3